Lung pathology: illuminating insights with real-life cases - Abdul Aziz, Mardiana; Bakar, Nor Salmah; Mohd Azraai, Awla; Munshi, Muhammad Afif; Mohd Hatta, Nurfareha (Faculty of Medicine, 2024)
On 29th February 2024, the Department of Pathology, Faculty of Medicine, UiTM conducted an online webinar entitled ‘Lung Pathology – Illuminating Insights with Real-Life Cases’. The speaker was Professor Dr Maxwell Smith, an Anatomic Pathology Consultant and Chair of Anatomic Pathology, Department of Laboratory Medicine and Pathology at the renowned Mayo Clinic, Arizona, USA.